Representasi Mitos dan Ideologi Perempuan dalam Film Televisi Suara Hati Istri - Sunaryanto, Sunaryanto (Universitas Indraprasta PGRI, 2023)
The presence of media in various forms ranging from television to social media in the internet era cannot completely change the position of women who are stereotyped in a bad way. For example, women in the household are represented in the media as a group that is weak, powerless, and unable to determine their own future. This research uses qualitative research with a critical paradigm which is part of media studies and cultural studies. The data collection method was carried out by observing the text of the FTV Voice of the Wife's Heart